Composition dependence of structural and piezoelectric properties in Bi(Mg0.5Ti0.5)O3-modified BaTiO3-BiFeO3 ceramics. (1st November 2022) - Nam, Hyunwook; Fujii, Ichiro; Kim, Sangwook; Ishii, Takaaki; Ueno, Shintaro; Khanal, Gopal Prasad; Kuroiwa, Yoshihiro; Wada, Satoshi
Abstract: The chemical composition dependence of the Bi(Mg0.5 Ti0.5 )O3 (BMT)-modified BaTiO3 (BT)-BiFeO3 (BF) ceramics fabricated by a solid-state synthesis was studied. The effects of BT/BF ratios and BMT concentration on the crystal structure, piezoelectric, and ferroelectric properties were investigated. The crystal structure study carried out under the synchrotron radiation X-ray diffraction revealed a change from rhombohedral structure to the pseudo-cubic structure when the BT contents were increased. A significant change in crystal structure and piezoelectric characteristics was confirmed by varying the BT/BF ratios. In contrast, the crystal symmetry remained unaffected by varying the BMT concentration, while tailoring of the piezoelectric and ferroelectric properties was revealed. Based on the analysis of the structural characteristics and overall electrical properties, the ceramics with modification of the BMT content along with BT/BF ratios could be applied as candidate materials for various practical applications.